Investigation of the dB/dH effect using trapped flux in type II superconductors. - Wang, Sean X. (University of Ottawa (Canada), 1993)
Many workers visualize that, when magnetic flux first penetrates into type II superconductors, the flux line lattice exhibits a discontinuity of magnitude comparable to the lower critical field $H\sb{c1}$ over a dimension of the order of the penetration depth $\lambda$ along the front of the invading flux line lattice. This discontinuity is referred to as the dB/dH effect in the literature. Such a discontinuity is also thought to exist in the magnetic flux configuration (B profile) at the periphery of the specimen when the applied magnetic field $H\sb{a}$, which caused the flux lines to enter the specimen, is then removed. We have compared $\langle B\rangle\sb{rem}$, the amount of magnetic flux trapped in a sample after it has been subjected to an excursion (half cycle) of $H\sb{a}$ with $\langle B\rangle\sb{in}$, the amount of flux permeating the specimen at the peak of a half cycle of $H\sb{a}$. Such measurements were performed on six conventional type II superconductors in the form of long solid cylinders and ribbons. These observations are compared with critical state model predictions which incorporate discontinuities in the B profile of various magnitude ranging from zero to $B\sb{c1}$ and beyond. We show that the presence of any such discontinuities will be dramatically evident in graphs of $\langle B\rangle\sb{rem}$/ $\langle B\rangle\sb{in}$ versus $\langle B\rangle\sb{in}$. Plots of the data in this format indicate quite clearly that discontinuities are not present.
Keywords: Physics, Condensed Matter.